2004
DOI: 10.1523/jneurosci.2542-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ΔFosB in Reward-Related Brain Structures after Chronic Stress

Abstract: Acute and chronic stress differentially regulate immediate-early gene (IEG) expression in the brain. Although acute stress induces c-Fos and FosB, repeated exposure to stress desensitizes the c-Fos response, but FosB-like immunoreactivity remains high. Several other treatments differentially regulate IEG expression in a similar manner after acute versus chronic exposure. The form of FosB that persists after these chronic treatments has been identified as ⌬FosB, a splice variant of the fosB gene. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
245
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(265 citation statements)
references
References 61 publications
17
245
2
1
Order By: Relevance
“…It is thought that the VH modulates the hypothalamic-pituitary-adrenal axis, producing an inhibition of this pathway following stress (Herman et al, 1998;Mitchell and Goldman, 2004). Interestingly, it has recently been shown that chronic stress increases the expression of DFosB in several of the brain regions in which we observed an increase in DFosB following neonatal VH lesions, such as the mPFC, caudate putamen, and nucleus accumbens (Perrotti et al, 2004). It is therefore possible that VH lesions produce a state of enhanced responsiveness to stress resulting in comparable alterations in the activity or neuroendocrine and neuronal pathways that mediate stress-induced increase in DFosB expression.…”
Section: Functional Implications Of Dfosb Expressionsupporting
confidence: 54%
“…It is thought that the VH modulates the hypothalamic-pituitary-adrenal axis, producing an inhibition of this pathway following stress (Herman et al, 1998;Mitchell and Goldman, 2004). Interestingly, it has recently been shown that chronic stress increases the expression of DFosB in several of the brain regions in which we observed an increase in DFosB following neonatal VH lesions, such as the mPFC, caudate putamen, and nucleus accumbens (Perrotti et al, 2004). It is therefore possible that VH lesions produce a state of enhanced responsiveness to stress resulting in comparable alterations in the activity or neuroendocrine and neuronal pathways that mediate stress-induced increase in DFosB expression.…”
Section: Functional Implications Of Dfosb Expressionsupporting
confidence: 54%
“…The stressors, which varied from day to day for a period of 10 days, were administered according to an established paradigm (Willner et al, 1992;Ortiz et al, 1996;Perrotti et al, 2004). This stress paradigm has been previously shown to produce profound effects on a number of cellular, biochemical, and neurochemical end points (Willner et al, 1992;Ortiz et al, 1996;Perrotti et al, 2004).…”
Section: Stress and Drug Treatmentsmentioning
confidence: 99%
“…The primary goals of this study were: (1) to examine the influence of a 10-day repeated unpredictable stress (RUS) paradigm (Willner et al, 1992;Ortiz et al, 1996;Perrotti et al, 2004) on expression of Bcl-2, Bcl-xl, and Bax mRNAs and (2) to investigate whether treatment with clinically effective antidepressants from distinct pharmacological classes, as well as repeated electroconvulsive seizures (ECS), regulates expression of the apoptotic genes. We extend our analyses from cortex and hippocampus to include previously uncharacterized hypothalamic-limbic brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Viral-mediated gene transfer was performed as previously described (Carlezon et al, 1998;Perrotti et al, 2004). In short, cDNAs encoding the specific proteins were inserted into the herpes simplex virus (HSV) amplicon HSV-PrPUC and packaged into the virus using the helper 5dl1.2.…”
Section: Viral Vectorsmentioning
confidence: 99%